Critical Perspectives on UK Prisons - Quinlan, Christina (The prison journal, 2022)
This special issue of The Prison Journal features the scholarship of faculty based at, or associated with. the Institute for Research in Criminology, Community, Education and Social Justice at De Montfort University (DMU), Leicester, UK. Three articles offer critical perspectives on women's prisons, the role of coercive control in the lives of women offenders who are victimized by domestic abuse, and the issue of ethical research practice with imprisoned women. The remaining three contributions include an assessment of prison education in UK prisons, an overview of a hope-inspired UK prison arts program, and the results of a public attitudes survey regarding access to and use of digital technologiesby incarcerated individuals in the UK.